Strategi Guru Profesional dalam Meningkatkan Kualitas Pembelajaran Guru Muhamadiyah di SD Muhamadiyah - Amanda Sari; Bela Selviana; Adinda Efrillia Ananta Putri; Khasbi Ainun Najib (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the steps to become a professional teacher in improving the quality of Muhammadiyah teacher learning at SD Muhammadiyah Harjowinangun. Professional teachers are required to have balanced pedagogical, personality, social, and professional competencies. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the steps taken include: improving competency through training and workshops, strengthening character and integrity, implementing innovative learning methods, utilizing educational technology, and continuous evaluation and reflection on the learning process. These efforts have a positive impact on the quality of learning in the classroom, as seen from the increasing active participation of students and the achievement of learning outcomes. Thus, systematic efforts in building teacher professionalism contribute directly to improving the quality of education in the SD Muhammadiyah Harjowinangun environment.